The impact of tumor localization on prognosis of the patients following liver transplantation for hepatocellular carcinoma (Annals of Medical Research, 2021)
Aim: Hepatocellular carcinoma usually occurs in the setting of liver cirrhosis and therefore, resection is not possible in majority of the cases. Orthotopic liver transplantation (OLS) is a gold standard treatment option in hepatocellular carcinoma. The aim of the present retrospective study was to evaluate the prognosis of hepatocellular carcinoma localized in left or right side of the liver in patients who underwent OLS. Materials and Methods: 120 patients received OLS for hepatocellular carcinoma between 2007 and 2018 in the institute of liver transplantation. Tumors that were centrally located were excluded from the analysis. The remaining 104 patients were divided into two groups; Group 1 (right lobe, n=85 [81.7%]), Group 2 (left lobe, n=19 [18.3%]). The clinical and demographic data of the patients along with preoperative laboratory values such as alpha fetoprotein (AFP), gamma-glutamyl transpeptidase (GGT) and thrombocyte count were retrospectively evaluated. Results: The Median age in Group 1 and 2 were 54 (4-72) and 50.5 (37-68) years, respectively. Preoperative AFP levels in Group 1 and 2 were 9.25 (1-10800) ng/ml and 13 (1.5-317) ng/ml, respectively. The Model for end stage liver disease (MELD) scores in Group 1 and 2 were 12 (6-52) and 9 (6-21), respectively. None of the clinical, demographic and laboratory values along with disease-free survival, early mortality and recurrence were significantly different among the study groups (p>0.05). Conclusions: Although there is a big discrepancy in terms of patient’s numbers in right and left-sided tumors, our data failed to show any survival difference among the groups. Further studies, especially in hepatocellular carcinoma beyond the Milan criteria, are needed to validate our results.
Keywords: Hepatocellular carcinoma; liver; milan criteria; transplantation